Insight into the Physiopathologic Mechanism for the Coexistence of Depression and Osteoporosis - Wu, Ying; Yang, Yi; Wu, Haishan; Zhang, Beibei; Tang, Hui; Zhao, Jingping; Chen, Jindong (Current Signal Transduction Therapy, 2015)
Osteoporosis was related with depression especially in patients treated with psychotropic medicine. Selective serotonin reuptake inhibitors (SSRIs), the first-line treatment of depression, could up-regulate the extracellular serotonin (5-HT) levels and affect the serotonin system in bone metabolism. 5-HT transporter5-HTT) knockout results in bone mass decreased, architecture altered and mechanical properties impaired. Antidepressant-induced osteoporosis has direct and dose-dependent effects. Thus depression patients should evaluate skeletal system and receive antiosteoporotic treatments regularly, particularly during use of SSRI. But some reports have shown a dissociation of Major depressive disorder (MDD) and bone mineral density (BMD). The relationship between depression, BMD and bone metabolism remains elusive. Further studies will be tackled by ‘OMICS’ to understand possible mechanisms and develop new antidepressant for MDD.
Keywords: osteoporosis